Stature estimation from anthropometric head measurements in adults: South Indian populations - K., Vishal; Abirami, S.; Ganesh, R. (International Journal Of Community Medicine And Public Health, 2026)
Anthropometric evaluation of head and craniofacial dimensions is a cornerstone of human biological research with important applications in forensic science, clinical medicine, ergonomics and anthropology. South Indian populations exhibit substantial biological and sociocultural diversity making population-specific cranial reference standards. This review critically synthesizes existing literature on head anthropometry in South Indian adults focusing on biological determinants, regional variability and practical applications. The evidence indicates that adult head dimensions demonstrate relative post-maturity stability with limited age-related remodeling. The review highlights the relevance of head anthropometry in forensic identification, including sex determination, population affinity assessment and disaster victim identification. Emerging directions such as multicentric studies, three-dimensional imaging, artificial intelligence based morphometric analysis.